Private business in developing countries improved prospects - Pfeffermann, Guy Pierre; International Finance Corporation (Washington, D.C. World Bank, 1988)
After decades of growing state involvement in development, and many years of government hostility to private foreign investment, things have been changing over the past few years, and business prospects in the developing countries have taken a distinct turn for the better. This paper deals with this historic improvement which is part of the world wide efforts at structural adjustment. It addresses the question of what lies in store for private business. Particular attention is paid to recent trends in foreign direct investment and to privatization efforts.
Electronic reproduction.
Keywords: Business enterprises -- Developing countries; Investments, Foreign -- Developing countries; Privatization -- Developing countries; Electronic books